2018
DOI: 10.3390/cancers10090308
|View full text |Cite
|
Sign up to set email alerts
|

Cariprazine, A Dopamine D2/D3 Receptor Partial Agonist, Modulates ABCG2-Mediated Multidrug Resistance in Cancer

Abstract: Multidrug resistance (MDR) is a continuing clinical problem that limits the efficacy of chemotherapy in cancer. The over expression of the ATP-binding cassette (ABC) family G2 (ABCG2) transporter is one of the main mechanisms that mediates MDR in cancer. Molecular modeling data indicated that cariprazine, a dopamine D2/D3 receptor partial agonist, had a significant binding affinity for ABCG2 transporter with a Glide XP score of −6.515. Therefore, in this in vitro study, we determined the effect of cariprazine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The cells were further incubated with MTT for 4 hrs to produce the formation of the purple formazan crystals, which is indicative of viable cells. DMSO was added to dissolve the crystals and the absorbance was determined at 570 nm wavelength as described previously [26]. The IC 50 was calculated and the selectivity of the compounds was determined by comparing survival in normal cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cells were further incubated with MTT for 4 hrs to produce the formation of the purple formazan crystals, which is indicative of viable cells. DMSO was added to dissolve the crystals and the absorbance was determined at 570 nm wavelength as described previously [26]. The IC 50 was calculated and the selectivity of the compounds was determined by comparing survival in normal cells.…”
Section: Methodsmentioning
confidence: 99%
“…The survival of ovarian cancer cells (A2780) in the presence of LM08 was further determined by colony formation assay as previously described in detail [26,27,28]. Briefly, A2780 cells were incubated with vehicle (0 μM) or LM08 (10 or 20 μM) for 24 hrs.…”
Section: Methodsmentioning
confidence: 99%
“…In another study, cariprazine, a D3-preferring D3/D2 receptor partial agonist used for the treatment of schizophrenia and bipolar disorder [ 160 ], was utilized in vitro in ABCG2-mediated multidrug-resistant non-small lung cancer (H460-MX20 cell line) and colon cancer cell line (S1M1-80). The authors reported that cariprazine synergistically enhanced the efficacy of the antineoplastic drug mitoxantrone by downregulating the expression of ABCG2 protein, with the exact molecular mechanism of this modulation remaining unknown [ 161 ].…”
Section: D3 Receptors’ Modulation and Cancer Treatmentmentioning
confidence: 99%
“…Likewise, ABCG2-mediated chemoresistance in MDR cells is reduced by 10 mM D 3 antagonists PG01037, NGB 2904, SB27 7011A, and U99194 (Hussein et al, 2017). Hussein et al (2018) later reported that cariprazine (which they termed a D 2 /D 3 partial agonist) had similar effects and suggested it might be repurposed for cancer chemotherapy. The concentrations required, however, were $1 mM, much higher than found clinically with maximal doses of the cariprazine, a drug that also has active metabolites that accumulate at even higher levels (Nakamura et al, 2016).…”
Section: R Receptor Signaling Mechanisms Andmentioning
confidence: 99%